O arquétipo materno sob a luz da psicologia analítica de C.G. Jung - Campanario, Elisa Villaça (Universidade Federal de São Carlos, 2024)
The analytic psychology, developed by Carl Gustav Jung has some of its basis on psychoanalysis, but created a way of its own by exploring some concepts like the collective unconscious, the archetypes and symbolism, themes that are investigated in this paperwork. The study of these themes in this monography takes as a focus the mother archetype, precisely because of the symbolic meaning of creation, death and rebirth and also because everybody has a mother. Considering, then, that the maternity experience exists universally, represented by our own mothers and essentially internalized in everyone of us, the relevance of the theme is considerable. To illustrate the coverage of the chosen archetype, the text passes by Demeter and Persephone's myth, which illustrates well the powers and ambivalences of such, taking as a metaphor the nature cycles, that govern, beyond our lives, the agriculture. Thereby, this monography observes how the force of the concepts studied by Jung crosses us as humans, since our beginnings until today and will continue to affect while there is humanity.
The maternal archetype in the light of analytical psychology of C.G. Jung
Keywords: Arquétipo; Arquétipo materno; Inconsciente coletivo; Simbolismo; Psicologia analítica; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA DO DESENVOLVIMENTO HUMANO